Desenvolvimento embrionário de Ouriços-do-mar da espécie Echinometra lucunter (Linnaeus, 1758) envolve influxo de cálcio através dos canais de cálcio sensíveis à voltagem - Leite, Jocelmo Cassio de Araujo (2011)
Ca2+ is an intracellular messenger that controls a wide range of physiological functions through changes in its cytosolic concentration ([Ca2+]c). The increase in [Ca2+]c is derived of mobilization from intracellular stores or influx through channels, especially voltage-gated (Cav), present on cell surface. According to scientific literature, sea urchins embryogenesis is a process induced exclusively by the release of Ca2+ from the endoplasmic reticulum, and Ca2+ influx is not necessary for this process. However, there are studies in several species of the animal kingdom where Ca2+ influx is crucial for embryogenesis. Therefore, the aim of this study was to evaluate the involvement of Ca2+ influx at fertilization and embryonic development of Echinometra lucunter, a species of sea urchins with wide distribution on Brazilian coast. Thereby, eggs and embryos of E. lucunter were treated with various pharmacological tools and fertilization and embryonic development were monitored. Incubation of gametes in Ca2+ free medium inhibited fertilization and embryo treatment with Ca2+ chelators blocked embryonic development, suggesting that extracellular Ca2+ is essential for both processes. Cav blockers nifedipine, diltiazem and verapamil were also effective in blocking fertilization and embryo development, showing the importance of these channels to embryogenesis of E. lucunter. Inhibitory effect on embryo development is not associated with modulation of ABC superfamily proteins, since embryonic development was not affected, even under inhibition of these proteins. Verapamil inhibitory effect was reversed by prior addition of valinomycin which may be related to a probable increase of [Ca2+]c induced by K+ ionophore. ouabain, a Na+/K+-ATPase blocker that activates the reverse mode of Na+ /Ca2+, also reversed inhibition of development induced by verapamil. The reversal was not observed when compounds were added to embryos after verapamil, suggesting a temporal profile in inhibitory effect of these blockers. Inhibitory effects of verapamil and Ca2+ chelator EGTA were time-dependent, being absent 50 minutes after fertilization, suggesting that Ca2+ influx is seminal only in the first minutes of embryonic development. However, intracellular Ca2+ is essential for embryogenesis, since treatments with BAPTA-AM (chelator of intracellular Ca2+) and chlorpromazine or Trifluoperazine (Ca2+-calmodulin complex blockers) inhibited E. lucunter embryogenesis. Additionally, it was found that the rotundifolone, a plant-derived compound with vasorelaxing activity, attributed to the blockade of Cav, inhibited E. lucunter embryonic development showing an inhibitory profile similar to observed in vascular smooth muscle. Therefore, these results suggest that Ca2+ influx is essential for Echinometra lucunter embryogenesis and certify the embryonic development of this animal as appropriated pharmacological model for the investigation of natural and synthetic products that interferes in Ca2+ cellular dynamics.